A Randomized Controlled Trial on the Effects of Aerobic and Coordinative Training on Neural Correlates of Inhibitory Control in Children - Ludyga, Sebastian (J Clin Med, 2019)
Whereas aerobic training has found to be beneficial for inhibitory control, less is known on the efficiency of other exercise types in children. The present study compared the effects of aerobic and coordinative training on behavioral and neurophysiological measures of inhibitory control. Forty-five children were randomly assigned (1:1:1 ratio) to groups performing aerobic training, coordinative training or assisted homework sessions over 10 weeks. Before and after intervention, all participants completed a Flanker task. The P300 component of event-related potentials elicited from the task was recorded via electroencephalography. Additionally, aerobic fitness and gross-motor skills were assessed using 20 m Shuttle Run and Heidelberg Gross-Motor Test, respectively. Statistical analyses revealed no time by group interactions for the P300 component (amplitude, latency), p = 0.976, η(2) = 0.007, and behavioral performance (reaction time, accuracy), p = 0.570, η(2) = 0.045. In contrast, there was a significant group-difference in pre- to post-test changes in aerobic fitness, p = 0.008, η(2) = 0.246, with greater improvements following aerobic and coordinative training compared to assisted homework sessions. In conclusion, no differences regarding the efficiency of aerobic and coordinative training for the enhancement of inhibitory control were found as both exercise programs failed to elicit changes in speed and accuracy of stimulus evaluation and the allocation of attentional resources.